2019
DOI: 10.22270/jddt.v9i4-a.3459
|View full text |Cite
|
Sign up to set email alerts
|

Analytical method development and validation of Amlodipine besylate in tablet dosage form

Abstract: The  accurate and precise HPLC analytical method validated for the determination of Amlodipine besylate  in pharmaceutical dosage form.The chromatographic separation is carried out on shimadzu HPLC system (LC-2010 CHT)  with  UV Vissible  detector and C18(150mm x3.9 mm) 5 μm Column. The Mobile phase consists of Acetonitrile: Methanol: PH 3.0 Buffer (15 V: 35 V: 50 V) , at the flow rate  of  1.0 ml/min and elutes were monitoring  at 237 nm. The observed retention time for Amlodipine besylate was 10.8 min. The %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The obtained results coincide with similar studies by other authors. In particular, spectrophotometric methods for determining pure albendazole and in the composition of solid and liquid dosage forms are sensifast, economically available and subject to validation [6][7][8][9][10][11][12]. In the simultaneous determination of albendazole and other anthelmintic agents, for example, ivermectin, other researchers often turn to LC, GLC, and HPLC [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The obtained results coincide with similar studies by other authors. In particular, spectrophotometric methods for determining pure albendazole and in the composition of solid and liquid dosage forms are sensifast, economically available and subject to validation [6][7][8][9][10][11][12]. In the simultaneous determination of albendazole and other anthelmintic agents, for example, ivermectin, other researchers often turn to LC, GLC, and HPLC [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Additional dilutions of the standard stock solution were made with the mobile phase and the UV spectrum was scanned to acquire spectra. It was found that both albendazole and its primary impurity, Oxibendazole, exhibited significant absorption at 235 nm [8].…”
Section: Detection Of Wavelengthmentioning
confidence: 99%
“…2 Amlodipine besylate is chemically described as 3-ethyl-5-methyl (±)-2-[(2-aminoethox) methyl]-4-(2-chlorophenyl)-1, 4-dihydro-6-methyl-3, 5-pyridinedi carboxylate, mono benzene sulphonate. AML is a calcium channel blocker 2 , which inhibits the influx of extracellular calcium across the myocardial and vascular smooth muscle cell membranes, thus decreasing the contractile process and hence dilating coronary and systemic arteries 3 .…”
Section: Introductionmentioning
confidence: 99%